REASSERTING CONSERVATISM THROUGH USAID REFORM: CULTURAL POLITICS DISCOURSE IN PROJECT 2025’S “MANDATE FOR LEADERSHIP: THE CONSERVATIVE PROMISE” - Pratama, Rifka; Laksono, Arido; Falah, Fajrul; Subhan, Muhammad (Rubikon : Journal of Transnational American Studies, 2026)
The proposed reforms for the US Agency for International Development (USAID), as articulated in Project 2025’s “Mandate for Leadership: The Conservative Promise”, reflect the conservatives’ efforts to reconfigure the progressive values long upheld by liberal–democratic administrations in the US government. International aid is no longer viewed as a neutral humanitarian tool but as a strategic instrument of national interest. The reform proposal represents a contestation over cultural dominance, where competing political forces seek to legitimize their power through ideological control. This study employs a qualitative approach, analyzing policy documents “Mandate for Leadership: The Conservative Promise”, Section 2, Point 9 — pertaining to USAID. The analysis is conducted within the framework of cultural politics theory, wherein discourse—in both textual and oral forms—is conceptualized as a site of power and cultural contestation. The findings reveal that the proposed reforms to USAID constitute a systematic cultural–political strategy by the conservative bloc, aimed at realigning foreign aid priorities and ideologies.